Consumer Preference Analysis for Websites Using e-TailQ and AHP - Gaur, Loveleen; Anshu, Kumari (International Journal of Engineering and Technology, 2018)
In today’s scenario when the world is going online, websites are the first point of contact for the consumers. It has become a necessity to have a website nowadays to be effective and successful in this internet infiltrated world. A well-thought-out web design plan generates an extraordinary customer experience. In this paper we study the various scales and model given by researchers at different point of time related to website service quality. Here we have taken into consideration the e-Tail Quality (e-TailQ) scale for our study purpose. The model has five factors of online retailing customer experience: website layout, website information, reliability/customer service, fulfilment and security/privacy. These factors were then tested based on the Analytic Hierarchy Process (AHP) model which is based on an exponential scale to calculate each criterion’s relative weight. The research is an endeavor to move further in measuring customer preference towards the service qualities offered by the websites and developing a more focused approach.